2021
DOI: 10.1016/j.ajic.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Are saliva and deep throat sputum as reliable as common respiratory specimens for SARS-CoV-2 detection? A systematic review and meta-analysis

Abstract: Objective The COVID-19 pandemic raises an urgent need for large-scale control through easier, cheaper, and safer diagnostic specimens, including saliva and sputum. We aimed to conduct a systemic review and meta-analysis on the reliability and sensitivity of SARS-CoV-2 detection in saliva and deep throat sputum (DTS) compared to nasopharyngeal, combined naso/oropharyngeal, and oropharyngeal swabs. Methods This systematic review and meta-analysis was performed according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 69 publications
2
55
1
5
Order By: Relevance
“…swabs, wide-mouth tube, funnel, soother), or the target population (e.g. hospitalized inpatients, clinically suspected cases, symptomatic, asymptomatic, healthcare workers) [22,23]. To control the ongoing COVID-19 pandemic and to prevent the emergence of new foci of infection, the mass detection of symptomatic and asymptomatic individuals has become essential [24].…”
Section: Introductionmentioning
confidence: 99%
“…swabs, wide-mouth tube, funnel, soother), or the target population (e.g. hospitalized inpatients, clinically suspected cases, symptomatic, asymptomatic, healthcare workers) [22,23]. To control the ongoing COVID-19 pandemic and to prevent the emergence of new foci of infection, the mass detection of symptomatic and asymptomatic individuals has become essential [24].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain an enhanced saliva sample [ 19 , 20 ], patients with ARI were instructed and supervised by physicians to produce saliva coughed up from the posterior oropharynx (by clearing the throat or gargle) as this kind of sample seems to be much more sensitive than saliva from the oral cavity alone or from salivary glands [ 21 ]. However, recent studies suggested that oral cavity saliva specimens and deep throat sputum offer high sensitivity and specificity too [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we collected saliva coughed up from the posterior oropharynx (by clearing the throat or gargle). However, recent studies suggested that oral cavity saliva specimens and deep throat sputum also offer high sensitivity and specificity [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the gold standard nasopharyngeal swab, testing saliva for SARS-CoV-2 has been shown to have at least equal, and sometimes higher, sensitivity for detecting asymptomatic carriers (Savela et al, 2021;Yokota et al, 2021). Recent meta-analyses comparing the efficiency of PCR detection when applied to nasopharyngeal and saliva samples (Butler-Laporte et al, 2021;Cañete et al, 2021;Khiabani and Amirzade-Iranaq, 2021;Lee et al, 2021;Moreira et al, 2021), confirm the high specificity of saliva, with sensitivity positively correlating with stage of infection (i.e., early) and sampling technique (Tan et al, 2021).…”
Section: Saliva For Sars-cov-2 Infection Diagnosismentioning
confidence: 99%